1994
DOI: 10.1139/p94-155
|View full text |Cite
|
Sign up to set email alerts
|

Microwave spectrum and molecular structure of silacyclopropenylidene c-C2H2Si

Abstract: The rotational spectra of silacyclopropenylidene, c-C2H2Si, and its isotopic species (C2H229Si, C2D2Si, 13C2H2Si) were observed in the frequency region of 220–400 GHz by using a source-modulated microwave spectrometer combined with a free space absorption cell. c-C2H2Si was produced in the cell by discharging a mixture of SiH4, C2H2, and He. Least-squares analyses of the observed spectral lines yielded the rotational constants and the centrifugal distortion constants for the normal and its isotopic species. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…Although H 2 CSi has not been found in space [41], H 2 CCSi is a good candidate for astronomical discovery because it is much more polar ( ¼ 1:21 D versus $ 0:3 D) and because isovalent H 2 CCC has been detected in both interstellar and circumstellar sources. HSiCN and HSiNC were detected in the same molecular beam discharge source that produces strong lines of SiCN and SiNC, and precise spectroscopic constants were derived for each from the centimetre-wave data.…”
Section: Laboratory and Astronomical Discovery Of Newmentioning
confidence: 99%
“…Although H 2 CSi has not been found in space [41], H 2 CCSi is a good candidate for astronomical discovery because it is much more polar ( ¼ 1:21 D versus $ 0:3 D) and because isovalent H 2 CCC has been detected in both interstellar and circumstellar sources. HSiCN and HSiNC were detected in the same molecular beam discharge source that produces strong lines of SiCN and SiNC, and precise spectroscopic constants were derived for each from the centimetre-wave data.…”
Section: Laboratory and Astronomical Discovery Of Newmentioning
confidence: 99%
“…The microwave spectra of Si-1S and Si-3S have also been published. 6,21 Subsequent higher level theoretical studies have followed. 6,[22][23][24][25][26] Much less research [27][28][29][30][31] has been reported on the isovalent germanium systems.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a total of four C 2 H 2 Si and CNHSi molecules were also studied by high resolution spectroscopic techniques, i.e., microwave-and millimeter-wave spectroscopy. The millimeter wave spectrum of silacyclopropenylidene ͑1͒ was reported 10 as was a Fourier transform microwave ͑FTMW͒ study of H 2 CCSi ͑2͒. 11 In case of CNHSi structural isomers, HSiCN ͑7͒ and HSiNC ͑8͒ were identified in the gas phase through FTMW spectroscopy.…”
Section: Introductionmentioning
confidence: 99%